Linking Language and Events: Spatiotemporal Cues Drive Children's Expectations About the Meanings of Novel Transitive Verbs. Issue 1 (2nd January 2017) - Kline, Melissa; Snedeker, Jesse; Schulz, Laura
ABSTRACT: How do children map linguistic representations onto the conceptual structures that they encode? In the present studies, we provided 3–4-year-old children with minimal-pair scene contrasts in order to determine the effect of particular event properties on novel verb learning. Specifically, we tested whether spatiotemporal cues to causation also inform children's interpretation of transitive verbs either with or without the causal/inchoative alternation ( She broke the lamp/the lamp broke ). In Experiment 1, we examined spatiotemporal continuity. Children saw scenes with puppets that approached a toy in a distinctive manner, and toys that lit up or played a sound. In the causal events, the puppet contacted the object, and activation was immediate. In the noncausal events, the puppet stopped short before reaching the object, and the effect occurred after a short pause (apparently spontaneously). Children expected novel verbs used in the inchoative transitive/intransitive alternation to refer to spatiotemporally intact causal interactions rather than to "gap" control scenes. In Experiment 2, we manipulated the temporal order of sub-events, holding spatial relationships constant, and provided evidence for only one verb frame (either transitive or intransitive). Children mapped transitive verbs to scenes where the agent's action closely preceded the activation of the toy over scenes in which the timing of the two events was switched, but did not do so when they heard an intransitive construction. These studies reveal that children's expectations about transitive verbs are at least partly driven by their nonlinguistic understanding of causal events: children expect transitive syntax to refer to scenes where the agent's action is a plausible cause of the outcome. These findings open a wide avenue for exploration into the relationship between children's linguistic knowledge and their nonlinguistic understanding of events.